Knowledge Discovery Techniques in Human Talent Management: “A Knowledge Discovery Databases Approach to Conquer Employee Attrition Problem Using Data Mining Techniques” - Tripathi, KP; Gaur, Ashutosh (International Journal of Computer Sciences and Engineering, 2019)
Talent resource management is one of the complex tasks for human resource professionals to assign the right person for the right place at the right time in the organization. The sustainability of suitable employee in an organization is very crucial these days. In this competitive age, employees are switching the organization on some gain but the organization suffers a lot. This paper is mainly concerned with the application of the knowledge discovery technique in human resource management, particularly in talent resource management to conquer the employee attrition and predicting the possible attrition in future.